Practices and funding opportunities of national parks in Northern Finland : a future oriented approach on entry fees - Rossinen, Elias (fi=Lapin yliopisto|en=University of Lapland|, 2024)
The purpose of this study was to find out would it be reasonable to use entry fees to enter a Finnish national park or is the current practice of free entry the most suitable option or some other practice like voluntary fees. Such issues like over-crowdedness and funding issues with the manager of the parks, Metsähallitus are something that it has be able to deal with at the moment or in the future, which is why a demand for such study was evident. Also, similar studies were not made in a Finnish context while recently discussions about the use of entry fees have become more and more relevant as the government of Finland has taken a policy for cutting all possible costs to balance the state budget. Globally, national parks are facing decreases in state funding year after year – thus a mandatory entry fee has become a common practice elsewhere in many countries to cover the costs of the national park consumption and management. The main research question of the study was: What is expected to happen if Finnish national parks would start to charge entry fees for entering a national park? This question and related sub-questions were attempted to find answers to with a qualitative approach using semi-structured interviews and summative content analysis as the research methods of this study. The study was carried out with a predictive future research approach while considering social constructivism as the underlying social paradigm of the study. The study was lying on practice theory as a theoretical background of the study. Also, previous research on national park funding globally and in Finnish context were studied to find a research gap. Eventually, eight experts from Finnish national park and forestry industry were interviewed to collect the research data of the study. After analyzing the research data, the results show that the current practice of free entry in Finnish national parks is the practice to be continued with. However, voluntary entry fee practice can be attempted if it is found lawful and justified. ...